Biotic filtering by species' interactions constrains food‐web variability across spatial and abiotic gradients. (14th March 2022) - Bauer, Barbara; Berti, Emilio; Ryser, Remo; Gauzens, Benoit; Hirt, Myriam R.; Rosenbaum, Benjamin; Digel, Christoph; Ott, David; Scheu, Stefan; Brose, Ulrich
Abstract: Despite intensive research on species dissimilarity patterns across communities (i.e. β‐diversity), we still know little about their implications for variation in food‐web structures. Our analyses of 50 lake and 48 forest soil communities show that, while species dissimilarity depends on environmental and spatial gradients, these effects are only weakly propagated to the networks. Moreover, our results show that species and food‐web dissimilarities are consistently correlated, but that much of the variation in food‐web structure across spatial, environmental, and species gradients remains unexplained. Novel food‐web assembly models demonstrate the importance of biotic filtering during community assembly by (1) the availability of resources and (2) limiting similarity in species' interactions to avoid strong niche overlap and thus competitive exclusion. This reveals a strong signature of biotic filtering processes during local community assembly, which constrains the variability in structural food‐web patterns across local communities despite substantial turnover in species composition. Abstract : Our analyses of 50 lake and 48 forest soil communities show that, while species dissimilarity depends on environmental and spatial gradients, these effects are only weakly propagated to the networks. Moreover, our results show that species and food‐web dissimilarities are consistently correlated, but that much of the variation in food‐web structure across spatial, environmental, and species gradients remains unexplained. Our results also reveal a strong signature of biotic filtering processes during local community assembly, which constrains the variability in structural food‐web patterns across local communities despite substantial turnover in species composition.